Superolateral Hoffa's Fat Pad Edema in Collegiate Volleyball Players. Issue 6 (November 2015) - Mehta, Kaushal; Wissman, Robert; England, Eric; D'heurle, Albert; Newton, Keith; Kenter, Keith
Abstract : Objective: Superolateral Hoffa's fat pad (SHFP) edema is a previously described magnetic resonance (MR) finding located between the patellar tendon and the lateral femoral condyle. The purpose of our study was to determine the prevalence and clinical significance of SHFP edema in female collegiate volleyball players. Materials and Methods: Sixteen female collegiate volleyball players were consented for bilateral knee evaluations which consisted of history, physical examination and MR imaging. Each MR study was reviewed for the presence of SHFP edema, and 6 patellar maltracking measurements were done. These were tibial tuberosity-trochlear groove distance, patellar translation, lateral patellofemoral angle, trochlear depth, trochlear sulcus angle, and lateral trochlear inclination angle. Results: A total of 16 athletes, 32 knees (16 girls; age range, 18–22 years; mean, 19.9) were enrolled in the study. Sixteen knees (50%) in 8 athletes had SHFP edema, with 100% bilaterality; 16 knees in 8 athletes had no evidence of SHFP edema (50%). Functional outcomes and physical examination findings were within normal limits for all athletes with no difference noted between SHFP edema-positive and -negative individuals. There was a statistically significant difference in the tibial tuberosity-trochlear groove distance, patellar translation, and patellofemoral angle ( P value of < 0.001, 0.03 and 0.01, respectively) between the SHFP edema-positive and -negative individuals. Conclusions: Elite female volleyball athletes have a very high prevalence of SHFP edema, which is always bilateral. Although the exact etiology of SHFP edema remains inconclusive, it could potentially be a sensitive indicator of subtle patellar maltracking which cannot be distinguished by history and physical examination findings. Given the very high prevalence of SHFP edema and this being an asymptomatic finding, there is likely little clinical significance of this in majority of high-performance athletes.